Analisis Pengaruh Konsentrasi Ragi dan Waktu Fermentasi Terhadap Nilai Gizi dan Aktivitas Antioksidan Tempe Kedelai Kombinasi Kacang Roay (Phaseolus lunatus L) - AI PADHILAH FAUZIAH; ASEP SUPRIADIN; ASSYIFA JUNITASARI (UIN Sunan Gunung Djati Bandung, 2022)
Tempeh is a fermented food product that has the potential as a source of antioxidants and contains several nutrients needed by the body. The existence of innovation in terms of raw materials, namely the addition of other types of beans such as lima beans (Phaseolus lunatus L) has the potential to minimize soybean imports from outside. There are two factors that can affect the quality of tempeh during the fermentation process, namely the concentration of added yeast and also the length of fermentation time, so it is necessary to do research on the effect of these two factors. The method used in this study was a Randomized Block Design (RBD) with 2 factors and 2 repetitions. The first factor is yeast concentration with 3 variations (1.5%, 2% and 2.5%) and the second factor is fermentation time with 3 variations (42 hours, 48 hours and 54 hours). Furthermore, the analysis of the influence of these two factors on nutritional value using the proximate method (including water content, ash content, fat content, protein content and carbohydrate content), antioxidant activity using the DPPH method and organoleptic tests. The results showed that the addition of yeast concentration and fermentation time had a significant effect on the nutritional value, antioxidant activity and organoleptic. The best treatment was obtained in soybean tempeh combination of lima beans with the addition of 2.5% yeast concentration and 42 hours fermentation time, namely water content 60.92%, ash content 0.76%, fat content 1.33%, protein content 31.45%. and carbohydrate content of 5.54%, antioxidant activity of 34.23% and based on organoleptic tests are preferred and acceptable among the public.